Technology Literacy of Vocational Students in CAD Learning Materials: A Study at Private and Public Mechanical Engineering Vocational Schools - Saputra, Nisa Aulia; Hamidah, Ida; Setiawan, Agus; Riza, Lala Septem; Matsumoto, Toru (Journal of Technical Education and Training, 2025)
In today’s digital era, technological literacy is a crucial competency, particularly in vocational education where tools like Computer-Aided Design (CAD) are essential for workforce readiness. However, students often face challenges in mastering CAD due to limited technological and graphical skills. This study investigates the level of technology literacy in CAD learning among vocational students from four private and two public schools in West Java, Indonesia. Using a cross-sectional survey method, data were collected via Google Forms from 118 Grade 12 students preparing for competency examinations. The findings revealed that most students demonstrate only a basic understanding of technological principles. Private school students generally outperformed their public-school counterparts, raising concerns about disparities in competency, especially regarding CAD proficiency. Interestingly, factors such as high motivation, adequate school facilities, and supportive environments did not significantly influence students’ technology literacy levels. This suggests that external conditions alone are insufficient to enhance technological capabilities. Instead, the findings highlight the importance of targeted interventions to address these gaps. In conclusion, the study underscores the need for improved instructional models, access to updated learning resources, and enhanced teacher training to strengthen students’ technological literacy and better prepare them for CAD-related demands in vocational contexts